Peer review of the pesticide risk assessment of the active substance chlorpropham. (26th July 2017) - ,; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Bellisai, Giulia; Brancato, Alba; Brocca, Daniela; Bura, Laszlo; Byers, Harry; Chiusolo, Arianna; Court Marques, Daniele; Crivellente, Federica; et al.
Abstract: The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, the Netherlands, and co‐rapporteur Member State, Spain, for the pesticide active substance chlorpropham and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of chlorpropham as a plant growth regulator on potatoes and as a herbicide on glasshouse and field lettuce, field onion and field flower bulbs. MRLs were assessed in potato and animal commodities. The reliable end points, appropriate for use in regulatory risk assessment and the proposed MRLs, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.